1985
DOI: 10.1073/pnas.82.7.2082
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin VH gene structure and diversity in Heterodontus, a phylogenetically primitive shark.

Abstract: A mouse VH probe has been used to identify and isolate VH homologs in a DNA library of Heterodontus francisci (horned shark). The complete nucleotide sequence of one VH gene, HXIA, has been determined and found to exhibit striking organizational homology and nucleotide identity with mammalian prototype VH genes. Metric analysis of the complete sequence is consistent with the early phylogenetic diversification of framework and complementarity-determining regions (CDR). Both the predicted amino acid sequence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 36 publications
2
47
0
Order By: Relevance
“…Many of the VH genes are functional, as a recent study (43) revealed that the frequency of pseudogenes in the VH1-3 families in Xenopus is -30%, comparable to that found in the human system (27). With (38), suggesting that it could have been a primordial VH gene or that there may have been selective pressure to maintain this family throughout evolution.…”
Section: Discussionmentioning
confidence: 92%
“…Many of the VH genes are functional, as a recent study (43) revealed that the frequency of pseudogenes in the VH1-3 families in Xenopus is -30%, comparable to that found in the human system (27). With (38), suggesting that it could have been a primordial VH gene or that there may have been selective pressure to maintain this family throughout evolution.…”
Section: Discussionmentioning
confidence: 92%
“…DNA cross-hybridization approaches have proven effective in identifying immunoglobulin gene homologs in lower vertebrates (28,34); however, outside of mammals, only the avian TCR 3-chain gene has been identified in this manner (6). The considerable sequence diversity among TCR genes in mammalian species and within the TCR multigene families in a single species (31) (28,35).…”
Section: T Y L I L I C K S I F Y T I F I S T I a W K T K T S Y Smentioning
confidence: 99%
“…It is likely that TCR and MHC molecules evolved together early in the vertebrate Uneage. Genes that encode immunoglobulins were isolated firbm the horned shark in the 1980s (132). Interestingly, all three types of MHC loci found m higher vertebrates (class I, class IIA and class IIB) have been found in the shark (133).…”
Section: Comparative Aspectsmentioning
confidence: 99%